Visual Discrimination Task in Guppies Using a Simultaneous Matching-to-Sample Procedure - Gabriela Gjinaj; Marco Dadda; Maria Elena Miletto Petrazzini (Animals)
Cognitive abilities in fish have been widely demonstrated using experimental protocols commonly adopted with mammals and birds. Only a few studies have tested fish in the simultaneous match-to-sample task (sMTS), and mixed evidence regarding their capacity to solve the task has been reported. Here we investigated whether guppies (Poecilia reticulata) could discriminate stimuli based on their sameness in the sMTS where fish presented with a sample stimulus had to choose which of two simultaneously presented comparison stimuli matched it. We also assessed how performance was influenced by the training set size and stimulus type. Three experiments were conducted using three different sets of stimuli: two colors (red and green), two geometric shapes (circle vs. triangle); and multiple shapes. Performance was analyzed using binomial tests, t-tests, and generalized linear mixed models. The results showed that guppies learned to select the rewarding stimulus in a relatively limited number of trials and were successful in all experiments. Although no effect of the training set size was observed, guppies were more accurate when multiple stimuli were used. These findings support previous evidence suggesting that multiple training stimuli may improve generalization abilities and set the basis for future studies that adopt a delayed version of the task.